Variation in clinical care associated with weekend admission and discharge in psychiatric inpatient units - Williams,R; Farquharson,L; Rhodes,E; Dang,M; Lindsay,N; Quirk,A; Baldwin,D; Crawford,M (BJPsych Open, 2020)
BackgroundQuestions have been raised regarding differences in the standards of care that patients receive when they are admitted to or discharged from in-patient units at weekends.AimsTo compare the quality of care received by patients with anxiety and depressive disorders who were admitted to or discharged from psychiatric hospital at weekends with those admitted or discharged during the ‘working week’.MethodRetrospective case-note review of 3795 admissions to in-patient psychiatric wards in England. Quality of care received by people with depressive or anxiety disorders was compared using multivariable regression analyses.ResultsIn total, 795 (20.9%) patients were admitted at weekends and 157 (4.8%) were discharged at weekends. There were minimal differences in quality of care between those admitted at weekends and those admitted during the week. Patients discharged at weekends were less likely to be given sufficient notification (48 h) in advance of being discharged (OR = 0.55, 95% CI 0.39–0.78), to have a crisis plan in place (OR = 0.65, 95% CI 0.46–0.92) or to be given medication to take home (OR = 0.45, 95% CI 0.30–0.66). They were also less likely to have been assessed using a validated outcome measure (OR = 0.70, 95% CI 0.50–0.97).ConclusionsThere is no evidence of a ‘weekend effect’ for patients admitted to psychiatric hospital at weekends, but the quality of care offered to those who were discharged at weekends was relatively poor, highlighting the need for improvement in this area.